2010
DOI: 10.1007/s11013-010-9171-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Symptoms and Reported Trauma Among Patients with Spirit Possession and Matched Healthy Controls in Uganda

Abstract: Spirit possession is a common, worldwide phenomenon with dissociative features. Studies in Europe and the United States have revealed associations among psychoform and somatoform dissociation and (reported) potential traumatic events. The aim of this study was to explore the relationships among spirit possession, dissociative symptoms and reported potentially traumatizing events in Uganda. One hundred nineteen persons with spirit possession, diagnosed by traditional healers, were compared to a matched control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 59 publications
1
64
1
2
Order By: Relevance
“…Consistent with prior research (Ertl et al, 2010;Neuner et al, 2012;van Duijl et al, 2010), results revealed positive correlations of spirit possession symptom severity over lifetime with symptom severity of numerous trauma-related disorders such as PTSD symptom severity, TRAUMA-RELATED DISORDERS &SPIRIT POSSESSION 16 depression symptom severity, and shame and guilt feelings. Additionally, a positive correlation with psychotic symptom severity was found.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with prior research (Ertl et al, 2010;Neuner et al, 2012;van Duijl et al, 2010), results revealed positive correlations of spirit possession symptom severity over lifetime with symptom severity of numerous trauma-related disorders such as PTSD symptom severity, TRAUMA-RELATED DISORDERS &SPIRIT POSSESSION 16 depression symptom severity, and shame and guilt feelings. Additionally, a positive correlation with psychotic symptom severity was found.…”
Section: Discussionsupporting
confidence: 89%
“…Several explicitly trauma-related disorders emphasized the experience of anger and intense rage (e.g., West Papuan saki hati ; Rees & Silove, 2011). Spirit possession was reported in several African and Latin American studies (Betancourt, et al, 2009; Englund, 1998; van Duijl, Nijenhius, Komproe, Gernaat, & de Jong, 2010; Ventevogel, Jordans, Reis, & de Jong, 2013; Zur, 1996), with spirits of the dead revisiting trauma survivors and characterized symptomologically by intrusion, hyperarousal, and dissociation. Two CCDs drew upon hybrid explanatory models comprised of local conceptualizations and those brought by psychosocial humanitarian workers.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, sensorimotor dissociative symptoms were moderately to strongly correlated with reported adverse events, and in particular threat to the body and life itself, in every study with the Somatoform Dissociation Questionnaire (SDQ-20; Nijenhuis et al 1996;Nijenhuis 2009). The correlation was not mediated by absorption (Näring and Nijenhuis 2005), and existed in a variety of populations and cultures (e.g., Van Duijl et al 2010). Diseth (2006) documented that chronic invasive medical traumatization in very early childhood was the only predictor of sensorimotor dissociation in adolescence.…”
Section: Relationship To Adverse Eventsmentioning
confidence: 93%